Silver ethynide clusters constructed with fluorinated β-diketonate ligands. Issue 14 (22nd March 2018) - Jin, Jun-Ling; Shen, Yang-Lin; Xie, Yun-Peng; Lu, Xing
Abstract : Phosphonate can act as the intermediate connector to link two silver ethynide clusters functionalized by hfac ligands together to enlarge the silver cluster. Abstract : A fluorinated β-diketonate hexafluoroacetylacetone ligand has been employed to construct eight new silver ethynide clusters. Single crystal X-ray analysis revealed that complexes1–8 are functionalized by hexafluoroacetylacetones as terminal ligands. In compounds3–8, different kinds of silver ethynide cluster shells enclose various templates, respectively. In7 and8, the tert -butylphosphonate ligand functions as a tripodal strut to support the vertex-sharing or fusion of two small silver(i ) clusters to form an enlarged composite cluster.